Catalyst for preparing plasticizer alcohol through liquid-phase hydrogenation of olefine aldehyde and preparation method of catalyst

By using natural minerals containing SiO2 as support and nickel oxide and copper oxide as active components, the problem of insufficient stability of existing catalysts is solved, and high conversion, selectivity and long-term stability are achieved.

CN119425698APending Publication Date: 2025-02-14CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202310947357.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing catalysts used for liquid phase hydrogenation of enaldehyde to make plasticizer alcohols have insufficient stability, which makes it impossible to meet the needs in practical applications.

Method used

The catalyst is prepared by a specific preparation method using natural minerals containing SiO2 or acidified modified natural minerals containing SiO2 as support, and combined with nickel oxide and copper oxide as active components.

Benefits of technology

The stability of the catalyst is improved while maintaining excellent enole conversion and alcohol selectivity, ensuring the stability of the catalyst for long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004367022750000071
    Figure BDA0004367022750000071
  • Figure BDA0004367022750000081
    Figure BDA0004367022750000081
Patent Text Reader

Abstract

The invention discloses a catalyst for preparing plasticizer alcohol through liquid-phase hydrogenation of olefine aldehyde. The catalyst comprises an active component and a carrier, wherein the active components comprise nickel oxide and copper oxide, and the carrier is a natural mineral containing SiO2 or an acidified and modified natural mineral containing SiO2; based on the mass percentage of the catalyst, the content of the nickel oxide is 20-40%, the content of the copper oxide is 1-6%, and the balance is the carrier. According to the catalyst, the SiO2-containing natural mineral or the acidified and modified SiO2-containing natural mineral is used as the carrier, the SiO2-containing natural mineral carries the alkali metal or alkaline earth metal, so that an additive does not need to be additionally added when the catalyst is prepared, and meanwhile, the alkali metal or alkaline earth metal is carried by the carrier, so that the catalyst is not required to be additionally added. The catalyst prepared by the method is more uniform in distribution in the carrier and more stable in combination with the carrier, so that the preparation cost of the catalyst can be reduced, and the catalyst can be ensured to have excellent olefin aldehyde conversion rate, alcohol selectivity and use stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and particularly relates to a catalyst for preparing plasticizer alcohol by liquid-phase hydrogenation of olefinic aldehyde and a preparation method thereof. Background Art

[0002] In industry, aliphatic primary alcohols with a total molecular carbon number of 4 to 13 are generally referred to as plasticizer alcohols. The main varieties are: n-butanol, isobutanol, isohexanol, amyl alcohol, isoheptanol, n-octanol, isooctyl alcohol, 2-ethylhexanol, isononanol, n-decanol, isodecyl alcohol, 2-propylheptanol, isododecyl alcohol, isotridecanol, etc. Most of them are primary alcohols with Cl to C3 branches. At present, plasticizer alcohols are generally produced by carbonyl synthesis, that is, olefins are hydroformylated with carbon monoxide and hydrogen to produce aldehydes. Long-chain aldehydes often need to be condensed from two molecules of aldehyde. The condensed aldehyde molecules contain both C=C bonds and C=O bonds, and then hydrogenated to produce the corresponding alcohols. There are two ways of hydrogenation reaction: gas phase hydrogenation and liquid phase hydrogenation. Compared with gas phase hydrogenation, liquid phase hydrogenation has a more favorable energy balance and higher space-time yield and is widely used. However, due to the high concentration of both aldehyde and alcohol, liquid phase hydrogenation easily forms more by-products during the reaction process. Therefore, highly active and selective catalysts are the research focus of olefin aldehyde hydrogenation catalytic systems. In the prior art, industrial olefin aldehyde hydrogenation is commonly used with Ni as the main active component, SiO2 or Al2O3 as a carrier, and Mg as an auxiliary catalyst. For example, in the patent with publication number CN113019379A, entitled A Catalyst for Liquid Phase Hydrogenation of olefin aldehyde, its Preparation Method and Use, it is disclosed that the catalyst includes, by mass percentage: NiO is 10-30%, MgO is 0.5-15%, TiO2 is 0.5-15%, and the remainder is γ-Al2O3; wherein, the carrier is MgO / TiO2 / γ-Al2O3, the active component is Ni element, and the catalyst has high activity and high selectivity. However, in the actual application process, it was found that due to the capillary condensation phenomenon, the Mg distribution in the modified alumina carrier was uneven, resulting in the fact that the actual effect of the catalyst was not very obvious, resulting in the insufficient stability of the prepared catalyst, and it still could not meet people's needs in the actual application process. Summary of the invention

[0003] The present invention aims to solve the technical problem of insufficient stability of catalysts used for preparing plasticizer alcohols by liquid phase hydrogenation of olefinic aldehydes in the prior art; a catalyst used for preparing plasticizer alcohols by liquid phase hydrogenation of olefinic aldehydes and a preparation method thereof are proposed, so as to ensure that the catalyst has excellent olefinic aldehyde conversion rate and plasticizer alcohol selectivity while having good stability.

[0004] In order to achieve the above object, the present invention adopts the following technical scheme:

[0005] A catalyst for preparing plasticizer alcohol by liquid phase hydrogenation of olefinic aldehydes, comprising an active component and a carrier;

[0006] Wherein, the active components include nickel oxide and copper oxide, and the carrier is a natural mineral containing SiO2 or a natural mineral containing SiO2 modified by acidification;

[0007] Calculated by mass percentage of the catalyst, the nickel oxide content is 20-40%, the copper oxide content is 1-6%, and the rest is the carrier.

[0008] Furthermore, the natural mineral containing SiO2 is any one of kaolinite, diatomaceous earth, attapulgite, wollastonite, illite or sepiolite.

[0009] A method for preparing a catalyst for preparing plasticizer alcohol by liquid phase hydrogenation of olefinic aldehydes comprises the following steps:

[0010] Step 1, weighing a carrier by weight, wherein the carrier is a natural mineral containing SiO2 or a natural mineral containing SiO2 modified by acidification;

[0011] Step 2, weighing a soluble salt of an active metal by weight, putting the weighed soluble salt of the active metal into deionized water to mix into a solution, and then adding a precipitant to perform a precipitation reaction to obtain a precipitation reaction product;

[0012] Step 3, subjecting the precipitated reactant to constant temperature stirring, aging, and washing to obtain an active component slurry;

[0013] Step 4, adding the carrier weighed in step 1 to the active component slurry obtained in step 3, and performing slurrying, filtering and drying to obtain a semi-finished catalyst;

[0014] Step 5, weighing the adhesive according to weight, adding the weighed adhesive and the semi-finished catalyst obtained in step 4 into water for kneading, and then extruding and calcining to obtain the catalyst.

[0015] Furthermore, the acidification modification process of the natural mineral containing SiO2 is: adding the natural mineral containing SiO2 into an acidic modifier, mixing, stirring, and filtering; wherein the acidic modifier is a strong inorganic acid.

[0016] Furthermore, the soluble salt of the active metal is any one of Ni(NO3)2·6H2O and Cu(NO3)2·6H2O or a mixture of the two in any ratio.

[0017] Furthermore, the precipitant is one or a mixture of two or more of Na2CO3 solution, K2CO3 solution, NaOH solution, NH4HCO3 solution, (NH4)2CO3 solution or ammonia water in any proportion.

[0018] Furthermore, the reaction temperature during the precipitation reaction is 50-60° C., and the endpoint pH value of the precipitation reaction is 7.0-7.5.

[0019] Furthermore, the aging temperature of the constant temperature stirring aging is 50-60° C., and the aging time is 30-50 min.

[0020] Furthermore, the beating time is 20 to 30 minutes.

[0021] Furthermore, the adhesive is a cellulose-based adhesive, including methyl cellulose, carboxymethyl cellulose, hydroxymethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose or sodium carboxymethyl cellulose.

[0022] The beneficial effects of the present invention are:

[0023] The catalyst of the present invention adopts a natural mineral containing SiO2 or a natural mineral containing SiO2 modified by acidification as a carrier. Since the natural mineral containing SiO2 carries an alkali metal or an alkaline earth metal, no additional auxiliary agent needs to be added when preparing the catalyst, thereby reducing the preparation cost of the catalyst. At the same time, since the alkali metal or alkaline earth metal acting as an auxiliary agent is carried by the natural mineral containing SiO2, its distribution in the carrier is more uniform, and its combination with the carrier itself is more stable and not easy to be lost, thereby not only reducing the production cost of the catalyst, but also ensuring that the catalyst has excellent olefin aldehyde conversion rate, alcohol selectivity and stability in use. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be described more clearly and completely below. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meaning understood by people with general skills in the field to which the present invention belongs.

[0025] The words "first", "second" and similar words used in the patent application specification and claims of the present invention do not indicate any order, quantity or importance, but are only used to distinguish different components. Similarly, unless the context clearly indicates otherwise, the singular forms of "one", "an" or "the" and similar words do not indicate a quantitative limitation, but indicate the existence of at least one. Words such as "include" or "comprise" mean that the elements or objects appearing before "include" or "comprise" cover the features, wholes, steps, operations, elements and / or components listed after "include" or "comprise", and do not exclude the existence or addition of one or more other features, wholes, steps, operations, elements, components and / or their collections. "Up", "down", "left", "right" and the like are only used to indicate relative positional relationships. When the absolute position of the described object changes, the relative positional relationship may also change accordingly.

[0026] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0027] Example 1

[0028] A method for preparing a catalyst for preparing plasticizer alcohol by liquid phase hydrogenation of olefinic aldehydes comprises the following steps:

[0029] 200g Ni(NO3)2·6H2O and 10g Cu(NO3)2·6H2O were weighed and added to 0.5L deionized water to prepare a solution. The above-prepared solution and a Na2CO3 solution with a mass concentration of 8% were subjected to precipitation reaction in a precipitation tank with stirring. The precipitation temperature was controlled to be 50°C, the reaction neutralization time was 25min, and the precipitation end point pH value was 7.2; then stirred and aged at 55°C for 30min, 166g diatomaceous earth was added after washing and pulping for 20min, and then filtered and dried to obtain a semi-finished catalyst. Deionized water accounting for 8% of the weight of the semi-finished catalyst and 3g methyl cellulose were added to the semi-finished catalyst, and then kneaded, extruded, dried, and then roasted at 550°C for 2h to obtain catalyst sample H1. The catalyst contains 10.0wt% Ni, 1.0wt% Cu, 0.1wt% Na, 2.5wt% Al2O3, and the rest is carrier.

[0030] Example 2

[0031] A method for preparing a catalyst for preparing plasticizer alcohol by liquid phase hydrogenation of olefinic aldehydes comprises the following steps:

[0032] Weigh 95 g of diatomaceous earth, add it into 100 mL of 5% dilute sulfuric acid, stir for 5 min, then filter and wash to obtain modified diatomaceous earth for later use.

[0033] 400g Ni(NO3)2·6H2O and 10g Cu(NO3)2·6H2O were weighed and added to 1L deionized water to prepare a solution. The above-prepared solution and a K2CO3 solution with a mass concentration of 8% were subjected to precipitation reaction in a precipitation tank with stirring. The precipitation temperature was controlled to be 50°C, the reaction neutralization time was 20min, and the precipitation end point pH value was 7.1. Then, the mixture was stirred and aged at 55°C for 40min. After washing, the above-mentioned modified diatomaceous earth was added and slurried for 30min, and then filtered and dried to obtain a semi-finished catalyst. Deionized water accounting for 8% of the weight of the semi-finished catalyst and 7g methyl cellulose were added to the semi-finished catalyst, kneaded, extruded into strips, dried, and then roasted at 350°C for 2h to obtain a catalyst sample H2. The catalyst contained 40.0wt% Ni, 1.0wt% Cu, 0.1wt% K, 0.5wt% Al2O3, and the rest was a carrier.

[0034] Example 3

[0035] A method for preparing a catalyst for preparing plasticizer alcohol by liquid phase hydrogenation of olefinic aldehydes comprises the following steps:

[0036] 150g Ni(NO3)2·6H2O and 75g Cu(NO3)2·6H2O were weighed and added to 0.5L deionized water to prepare a solution. The above-prepared solution and a K2CO3 solution with a mass concentration of 8% were subjected to precipitation reaction in a precipitation tank with stirring. The precipitation temperature was controlled to be 55°C, the reaction neutralization time was 15min, and the precipitation end point pH value was 7.3; then stirred and aged at 55°C for 30min, 140g attapulgite powder was added after washing and slurrying for 20min, and then filtered and dried to obtain a semi-finished catalyst. Deionized water accounting for 8% of the weight of the semi-finished catalyst and 3g methyl cellulose were added to the semi-finished catalyst, and then kneaded, extruded, dried, and then roasted at 650°C for 2h to obtain catalyst sample H3. The catalyst contains 15.0wt% Ni, 8.0wt% Cu, 0.11wt% (Na+K), 1.2wt% Mg, and the rest is carrier.

[0037] Example 4

[0038] A method for preparing a catalyst for preparing plasticizer alcohol by liquid phase hydrogenation of olefinic aldehydes comprises the following steps:

[0039] Weigh 200 g of grey silica and add it into 2200 mL of 10% nitric acid, stir for 5 minutes, and then filter and wash to obtain modified grey silica for later use.

[0040] Weigh 280g Ni(NO3)2·6H2O and 95g Cu(NO3)2·6H2O and add 1L deionized water to prepare a solution. In a precipitation tank with stirring, the above-prepared solution and a K2CO3 solution with a mass concentration of 8% are subjected to precipitation reaction. The precipitation temperature is controlled at 50°C, the reaction neutralization time is 20min, and the precipitation end point pH value is 6.9. Then, the mixture is stirred and aged at 55°C for 40min. After washing, the above-mentioned modified gray silica is added and slurried for 30min, and then filtered and dried to obtain a semi-finished catalyst. Add 8% deionized water and 5g hydroxypropyl methylcellulose by weight to the semi-finished catalyst, knead, extrude into strips, dry, and then roast at 350°C for 2h to obtain catalyst sample H4. The catalyst contains 26.0wt% Ni, 10.0wt% Cu, 1.5wt% Ca, and the rest is carrier.

[0041] Example 5

[0042] A method for preparing a catalyst for preparing plasticizer alcohol by liquid phase hydrogenation of olefinic aldehydes comprises the following steps:

[0043] Weigh 220 g of kaolin and add it into 1200 mL of 30% nitric acid solution, stir for 5 minutes, then filter and wash to obtain modified kaolin for later use.

[0044] Weigh 360g Ni(NO3)2·6H2O and 10g Cu(NO3)2·6H2O and add 1L deionized water to prepare a solution. In a precipitation tank with stirring, the above-prepared solution and a Na2CO3 solution with a mass concentration of 8% are subjected to precipitation reaction. The precipitation temperature is controlled to be 55°C, the reaction neutralization time is 15min, and the precipitation end point pH value is 7.1. Then, the mixture is stirred and aged at 55°C for 30min. After washing, the above-mentioned modified kaolin is added and slurried for 30min, and then filtered and dried to obtain a semi-finished catalyst. Add 10% deionized water and 6g hydroxymethyl cellulose by weight to the semi-finished catalyst, knead, extrude into strips, dry, and roast at 350°C for 2h to obtain catalyst sample H5. The catalyst contains 36.0wt% Ni, 1.0wt% Cu, 0.1wt% Na, and the rest is carrier.

[0045] Example 6

[0046] A method for preparing a catalyst for preparing plasticizer alcohol by liquid phase hydrogenation of olefinic aldehydes comprises the following steps:

[0047] Weigh 340g Ni(NO3)2·6H2O and 40g Cu(NO3)2·6H2O and add 0.5L deionized water to prepare a solution. In a precipitation tank with stirring, the above-prepared solution and a K2CO3 solution with a mass concentration of 8% are subjected to precipitation reaction. The precipitation temperature is controlled to be 50°C, the reaction neutralization time is 20min, and the precipitation end point pH value is 7.0; then, the mixture is stirred and aged at 55°C for 30min, 100g illite powder is added after washing and slurrying for 20min, and then filtered and dried to obtain a semi-finished catalyst. After adding deionized water accounting for 8% of the weight of the semi-finished catalyst and 4g carboxymethyl cellulose, kneading, extrusion molding, drying, and then roasting at 550°C for 2h, the catalyst sample H6 is obtained. The catalyst contains 34.0wt% Ni, 4.0wt% Cu, 0.1wt% (Na+Ca), and the rest is carrier.

[0048] Example 7

[0049] A method for preparing a catalyst for preparing plasticizer alcohol by liquid phase hydrogenation of olefinic aldehydes comprises the following steps:

[0050] Weigh 210g Ni(NO3)2·6H2O and 58g Cu(NO3)2·6H2O and add 0.5L deionized water to prepare a solution. In a precipitation tank with stirring, the above-prepared solution and a Na2CO3 solution with a mass concentration of 8% are subjected to precipitation reaction. The precipitation temperature is controlled to be 50°C, the reaction neutralization time is 20min, and the precipitation end point pH value is 7.0; then, the mixture is stirred and aged at 55°C for 30min, and after washing, 128g of sea foam mud is added and slurried for 20min, and then filtered and dried to obtain a semi-finished catalyst. After adding deionized water accounting for 8% of the weight of the semi-finished catalyst and 3g of methyl cellulose, the mixture is kneaded, extruded, dried, and then roasted at 500°C for 2h to obtain a catalyst sample H7. The catalyst contains 21.0wt% Ni, 7.5wt% Cu, 2.0wt% (Mg+Na), and the rest is a carrier.

[0051] Example 8

[0052] A method for preparing a catalyst for preparing plasticizer alcohol by liquid phase hydrogenation of olefinic aldehydes comprises the following steps:

[0053] Weigh 60 g of diatomaceous earth, add it into 60 mL of 5% dilute sulfuric acid, stir for 5 min, then filter and wash to obtain modified diatomaceous earth for later use.

[0054] 400g Ni(NO3)2·6H2O and 10g Cu(NO3)2·6H2O were weighed and added to 1L deionized water to prepare a solution. The above-prepared solution and a K2CO3 solution with a mass concentration of 8% were subjected to precipitation reaction in a precipitation tank with stirring. The precipitation temperature was controlled to be 50°C, the reaction neutralization time was 20min, and the precipitation end point pH value was 7.1. Then, the mixture was stirred and aged at 55°C for 40min. After washing, the above-mentioned modified diatomaceous earth and 35g illite powder were added and slurried for 30min. Then, the mixture was filtered and dried to obtain a semi-finished catalyst. Deionized water accounting for 8% of the weight of the semi-finished catalyst and 7g hydroxymethyl cellulose were added to the semi-finished catalyst, kneaded, extruded into strips, dried, and roasted at 550°C for 2h to obtain a catalyst sample H8. The catalyst contained 39.0wt% Ni, 1.1wt% Cu, 0.1wt% K, 0.2wt% Al2O3, and the rest was a carrier.

[0055] Example 9

[0056] A method for preparing a catalyst for preparing plasticizer alcohol by liquid phase hydrogenation of olefinic aldehydes comprises the following steps:

[0057] Weigh 220 g of kaolin and add it into 1200 mL of 30% sodium hydroxide solution, stir for 30 min, then filter and wash to obtain modified kaolin for later use.

[0058] 370g Ni(NO3)2·6H2O and 20g Cu(NO3)2·6H2O were weighed and added to 1L deionized water to prepare a solution. The above solution was precipitated with a K2CO3 solution of 8% in a precipitation tank with stirring. The precipitation temperature was controlled at 50°C, the reaction neutralization time was 20min, and the precipitation end point pH value was 7.1. Then, the mixture was stirred and aged at 55°C for 40min. After washing, 50g of the above modified kaolin and 50g of sepiolite powder were added and mixed evenly to obtain a semi-finished catalyst. 12% deionized water and 20g carboxymethyl cellulose were added to the semi-finished catalyst by weight, kneaded, extruded into strips, dried, and roasted at 600°C for 2h to obtain a catalyst sample H9. The catalyst contained 36.0wt% Ni, 2.1wt% Cu, 0.8wt% Al2O3, 0.1wt% Mg, and the rest was carrier.

[0059] Comparative Example

[0060] The commercially available liquid phase aldehyde hydrogenation catalyst is SNCAT-2800TE.

[0061] Comparative test 1

[0062] In order to verify the catalytic effect of the catalysts obtained in Examples 1-9 and Comparative Examples for the catalytic hydrogenation of 2-propyl-2-heptenal in liquid phase, the catalysts obtained in the above Examples and Comparative Examples are now used for the catalytic reaction of 2-propyl-2-heptenal in liquid phase hydrogenation. The catalytic reaction process is: 50 mL of the catalyst samples in the above Examples 1-9 and Comparative Examples are respectively loaded into a fixed bed reactor, reduced with hydrogen, the reduction temperature is 450°C, and then under the conditions of pressure of 3-4MPa and temperature of 120-140°C, 2-propyl-2-heptenal and hydrogen are introduced, and the raw material liquid space velocity is 1.0h -1 The molar ratio of hydrogen to 2-propyl-2-heptenal is 100:1, and the gas after the reaction is condensed to obtain a liquid product. The liquid product is analyzed by gas chromatography, and the results are shown in Table 1.

[0063] Table 1 Catalyst activity test results for 2-propyl-2-heptenal liquid phase hydrogenation

[0064]

[0065]

[0066] Comparative test 2

[0067] In order to verify the catalytic effect of the catalysts obtained in Examples 1-9 and Comparative Examples for the catalytic hydrogenation of 2-ethylhexenal in liquid phase, the catalysts obtained in the above Examples and Comparative Examples are now used for the catalytic reaction of 2-ethylhexenal in liquid phase hydrogenation. The catalytic reaction process is as follows: 50 mL of the catalyst samples in the above Examples 1-9 and Comparative Examples are respectively loaded into a fixed bed reactor, reduced with hydrogen, the reduction temperature is 500°C, and then 2-ethylhexenal and hydrogen are introduced under the conditions of a pressure of 3-4 MPa and a temperature of 120-140°C, and the raw material liquid space velocity is 1.1 h -1 The molar ratio of hydrogen to 2-ethylhexenal is 300:1, and the gas after the reaction is condensed to obtain a liquid product. The liquid product is analyzed by gas chromatography, and the results are shown in Table 2.

[0068] Table 2 Catalyst activity test results for 2-ethylhexenal liquid phase hydrogenation

[0069] serial number 2-Ethylhexenal conversion rate % 2-Ethylhexanol selectivity % Catalyst stability / h H1 99.16 98.64 ≥1500 H2 98.83 99.23 ≥1500 H3 99.52 99.34 ≥1500 H4 99.32 99.26 ≥1500 H5 99.36 99.04 ≥1500 H6 98.76 98.79 ≥1500 H7 99.48 97.85 ≥1500 H8 99.35 99.24 ≥1500 H9 99.64 99.47 ≥1500 Comparative Example 99.27 98.43 ≥1000

[0070] Comparative test 3

[0071] In order to verify the catalytic effect of the catalysts obtained in Examples 1-9 and Comparative Examples for the catalytic hydrogenation of n-butyraldehyde in liquid phase, the catalysts obtained in the above-mentioned Examples and Comparative Examples are now used for the catalytic reaction of n-butyraldehyde in liquid phase hydrogenation. The catalytic reaction process is as follows: 50 mL of the catalyst samples in the above-mentioned Examples 1 to 9 and Comparative Examples are each taken and loaded into a fixed bed reactor, reduced with hydrogen, the reduction temperature is 400°C, and then n-butyraldehyde and hydrogen are introduced under the conditions of a pressure of 3 to 4 MPa and a temperature of 80 to 120°C, the raw material liquid space velocity is 1.1 h-1, the molar ratio of hydrogen to n-butyraldehyde is 200:1, and the gas after the reaction is condensed to obtain a liquid product. The liquid product is analyzed by gas chromatography, and the results are shown in Table 3.

[0072] Table 3 Catalyst activity test results for liquid phase hydrogenation of n-butyraldehyde

[0073] catalyst Butyraldehyde conversion rate % n-Butanol selectivity % Catalyst stability / h H1 98.16 98.73 ≥1500 H2 98.63 99.02 ≥1500 H3 99.12 99.15 ≥1500 H4 99.42 99.27 ≥1500 H5 99.16 99.34 ≥1500 H6 98.96 98.99 ≥1500 H7 99.48 99.05 ≥1500 H8 99.25 99.25 ≥1500 H9 99.54 99.36 ≥1500 Comparative Example 99.08 98.64 ≥1000

[0074] From the test data of the above examples, it can be seen that the catalyst prepared by the method of the present invention has a high aldehyde conversion rate and alcohol selectivity, and the catalyst has a high stability. Whether it is used for 2-propyl-2-heptenal liquid phase hydrogenation catalysis, or for 2-ethylhexenal or n-butyraldehyde liquid phase hydrogenation catalysis, the aldehyde conversion rate and alcohol selectivity can reach more than 99%, and the catalyst stability is greater than or equal to 1500 hours.

[0075] Finally, it should be noted that these embodiments are only used to illustrate the present invention and do not limit the scope of the present invention. In addition, for those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. The obvious changes or modifications derived from them are still within the scope of protection of the present invention.

Claims

1. A catalyst for preparing plasticizer alcohol by liquid phase hydrogenation of olefinic aldehydes, comprising an active component and a carrier; characterized in that: in, The active components include nickel oxide and copper oxide, and the carrier is a natural mineral containing SiO2 or a natural mineral containing SiO2 modified by acidification; Calculated by mass percentage of the catalyst, the nickel oxide content is 20-40%, the copper oxide content is 1-6%, and the rest is the carrier.

2. A catalyst for preparing plasticizer alcohol by liquid phase hydrogenation of alkenes according to claim 1, characterized in that: The natural mineral containing SiO2 is any one of kaolinite, diatomaceous earth, attapulgite, wollastonite, illite or sepiolite.

3. A method for preparing a catalyst for preparing plasticizer alcohol by liquid phase hydrogenation of olefinic aldehydes, characterized in that: The steps include: Step 1, weighing a carrier by weight, wherein the carrier is a natural mineral containing SiO2 or a natural mineral containing SiO2 modified by acidification; Step 2, weighing a soluble salt of an active metal by weight, putting the weighed soluble salt of the active metal into deionized water to mix into a solution, and then adding a precipitant to perform a precipitation reaction to obtain a precipitation reaction product; Step 3, subjecting the precipitated reactant to constant temperature stirring, aging, and washing to obtain an active component slurry; Step 4, adding the carrier weighed in step 1 to the active component slurry obtained in step 3, and performing slurrying, filtering and drying to obtain a semi-finished catalyst; Step 5, weighing the adhesive according to weight, adding the weighed adhesive and the semi-finished catalyst obtained in step 4 into water for kneading, extruding and calcining to obtain the catalyst.

4. A method for preparing a catalyst for preparing plasticizer alcohol by liquid phase hydrogenation of alkenal according to claim 3, characterized in that: The acidification modification process of the natural mineral containing SiO2 is as follows: adding the natural mineral containing SiO2 into an acidic modifier, mixing, stirring, and filtering; wherein the acidic modifier is a strong inorganic acid.

5. A method for preparing a catalyst for preparing plasticizer alcohol by liquid phase hydrogenation of alkenal according to claim 3, characterized in that: The soluble salt of the active metal is any one of Ni(NO3)2·6H2O and Cu(NO3)2·6H2O or a mixture of the two in any ratio.

6. A method for preparing a catalyst for preparing plasticizer alcohol by liquid phase hydrogenation of alkenal according to claim 3, characterized in that: The precipitant is one or a mixture of two or more of Na2CO3 solution, K2CO3 solution, NaOH solution, NH4HCO3 solution, (NH4)2CO3 solution or ammonia water in any proportion.

7. A method for preparing a catalyst for preparing plasticizer alcohol by liquid phase hydrogenation of alkenal according to claim 3, characterized in that: The reaction temperature during the precipitation reaction is 50-60° C., and the endpoint pH value of the precipitation reaction is 7.0-7.

5.

8. A method for preparing a catalyst for preparing plasticizer alcohol by liquid phase hydrogenation of alkenal according to claim 3, characterized in that: The aging temperature of the constant temperature stirring aging is 50-60° C., and the aging time is 30-50 min.

9. A method for preparing a catalyst for preparing plasticizer alcohol by liquid phase hydrogenation of alkenal according to claim 3, characterized in that: The beating time is 20 to 30 minutes.

10. The method for preparing a catalyst for preparing plasticizer alcohol by liquid phase hydrogenation of olefinic aldehydes according to claim 3, characterized in that: The adhesive is any one of methyl cellulose, carboxymethyl cellulose, hydroxymethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose or sodium carboxymethyl cellulose.

Citation Information

Patent Citations

  • Catalyst for liquid-phase hydrogenation of olefine aldehyde as well as preparation method and application of catalyst

    CN113019379A

  • Methanation catalyst and preparation method thereof

    CN111097534A

  • Catalyst for preparing alcohol through aldehyde hydrogenation, and preparation method thereof

    CN111215081A

  • Liquid phase hydrogenating catalyst, its preparation process and application

    CN1275439A

  • Technology of hydrogenatioin to produce iso octanol using iso octaldehyde mixture and its catalyst

    CN1478596A